Arabidopsis TNL-WRKY domain receptor RRS1 contributes to temperature-conditioned RPS4 auto-immunity - Heidrich, Katharina; Tsuda, Kenichi; Blanvillain-Baufumé, Servane; Wirthmueller, Lennart; Bautor, Jaqueline; Parker, Jane E. (Frontiers in Plant Science, 2013)
In plant effector-triggered immunity (ETI), intracellular nucleotide binding-leucine rich repeat (NLR) receptors are activated by specific pathogen effectors. The Arabidopsis TIR (Toll Interleukin1 receptor domain)-NLR (denoted TNL) gene pair, RPS4 and RRS1, confers resistance to Pseudomonas syringae pv tomato (Pst) strain DC3000 expressing the Type III-secreted effector, AvrRps4. Nuclear accumulation of AvrRps4, RPS4 and the TNL resistance regulator EDS1 is necessary for ETI. RRS1 possesses a C-terminal ‘WRKY’ transcription factor DNA binding domain suggesting that important RPS4/RRS1 recognition and/or resistance signaling events occur at the nuclear chromatin. In Arabidopsis accession Ws-0, the RPS4Ws/RRS1Ws allelic pair governs resistance to Pst/AvrRps4 accompanied by host programmed cell death (pcd). In accession Col-0, RPS4Col/RRS1Col effectively limits Pst/AvrRps4 growth without pcd. Constitutive expression of HA-StrepII tagged RPS4Col (in a 35S:RPS4-HS line) confers temperature conditioned EDS1-dependent auto-immunity. Here we show that a high (28oC, non-permissive) to moderate (19oC, permissive) temperature shift of 35S:RPS4-HS plants can be used to follow defense-related transcriptional dynamics without a pathogen effector trigger. By comparing responses of 35S:RPS4-HS with 35S:RPS4-HS rrs1-11 and 35S:RPS4-HS eds1-2 mutants, we establish that RPS4Col auto-immunity depends entirely on EDS1 and partially on RRS1Col. Examination of gene expression microarray data over 24h after temperature shift reveals a mainly quantitative RRS1Col contribution to up- or down-regulation of a small subset of RPS4Col-reprogrammed, EDS1-dependent genes. We find significant over-representation of WRKY transcription factor binding W-box cis-elements within the promoters of these genes. Our data show that RRS1Col contributes to temperature-conditioned RPS4Col auto-immunity and are consistent with activated RPS4Col engaging RRS1Col for resistance signaling.